ナンキョク ナイリクイキ ノ トウキ ノ ショウオン ゲンショウ ト タイリュウケン ノ ソウカン キボ ジュンカン - 平沢, 尚彦; ヒラサワ, ナオヒコ; Hirasawa, Naohiko (2010)
P(論文) 冬季の南極大陸の対流圏には成層圏から続く低温な極渦が形成される.総観規模の移動性擾乱の活動は強い傾圧性をもつ南極海上の極渦縁辺部で最も盛んで,南極内陸域に強い影響を及ぼすことは少ない.1997年にドームふじ基地(77゜S,40゜E)で行われた気象の強化観測では,極渦の低温に加え,その標高の高さと強い気温逆転層の影響も反映して,-70゜C以下の地上気温が観測されることが珍しくなかった.その中で冬季には,地上気温の変動が夏季に比べて大きくなった.6月には2日間で40゜Cにも及ぶ昇温現象があった(Hirasawa et al., 2000).この最も顕著だった昇温現象は,地上気圧上昇,地上風速増加,雲量増加を伴っていて,それらはブロッキングリッジに関連した総観規模大気循環に伴って暖湿大気がドームふじ基地上空へ移流したことにより引き起こされていた.このブロッキングリッジの形成にはロスビー波のエネルギー伝播が関係した.次に,1997年の冬季間(4-10月)について,ドームふじ基地の地上気温の時間変化から昇温現象を客観的に定義し,そこで抽出された17事例の特徴を調べた.多くの事例は地上気圧上昇,雲量増加を伴い,リッジ等の高気圧性大気循環の影響を受けていた.また,ブロッキングリッジに伴う6月の昇温現象が他の16事例に比べて,昇温の規模において突出していたことが示された. The atmosphere over the Antarctic interior is usually separated from the outside by circumpolar tight potential vorticity gradients, where surface transient eddies are embedded, at the Dome Fuji Station (77゜S, 40゜E) on the topographical ridge of the East Antarctic ice sheet, an intensive meteorological observation campaign was carried out in 1997, The daily surface air temperature at Dome Fuji Station in the winter was generally around -70゜C, influenced by a ground-based temperature inversion as well as lower temperature in the polar vortex, On the other hand, the air temperature varied with larger amplitude in winter than in summer, The most prominent fluctuation, which was warming to about -30゜C from -70゜C (approximately a 40゜C-warming for only 2 days), occurred in the second half of June (Hirasawa et al., 2000), The warming was accompanied with increments in surface pressure, surface wind speed, and cloud amount, They were induced by warm, moist air advection from outside of the continent, associated with a blocking ridge which was the leading edge of a quasi-stationary Rossby wave, The present research found 18 warming-events in the 1997 winter from April to October, including the one in June above, Most the warming-events were accompanied by increased surface pressure, surface wind speed, and cloud amount, and were associated with synoptic-scale anticyclonic circulations, respectively. departmental bulletin paper